v=x(10-2x)(3-2x)

Simple and best practice solution for v=x(10-2x)(3-2x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for v=x(10-2x)(3-2x) equation:


Simplifying
v = x(10 + -2x)(3 + -2x)

Multiply (10 + -2x) * (3 + -2x)
v = x(10(3 + -2x) + -2x * (3 + -2x))
v = x((3 * 10 + -2x * 10) + -2x * (3 + -2x))
v = x((30 + -20x) + -2x * (3 + -2x))
v = x(30 + -20x + (3 * -2x + -2x * -2x))
v = x(30 + -20x + (-6x + 4x2))

Combine like terms: -20x + -6x = -26x
v = x(30 + -26x + 4x2)
v = (30 * x + -26x * x + 4x2 * x)
v = (30x + -26x2 + 4x3)

Solving
v = 30x + -26x2 + 4x3

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Simplifying
v = 30x + -26x2 + 4x3

See similar equations:

| -3(x+7)=8 | | 49r^2=14r+8 | | 4+10s-2=9s+14-3s | | x^3/10-14x=2x^2/5 | | 3x-10-5x=-22 | | -1z+3.33=10 | | -d+12-3d=5d | | 8p+148p=15 | | -3=4a-a | | 2(x+5)=-x+2(x^2-5) | | 3y+9=48 | | -5.49+0.78=3.98 | | 3a*a=3+12a | | 1+6x=-5x+122 | | 1/4(18-a)=9.5 | | n+23=-24 | | 3v-v=14 | | -6(8-2a)=-92 | | 8-4=-7 | | x=3x+2.2(10-x) | | C=48m+0.99n | | 1+1=4z-10 | | 4x+x=750 | | 4(x-3)=8(x+2) | | 29+2b=5(b+4) | | 14+(35+36)= | | 6v-v=10 | | -40=32y-48 | | 8.164=2*3.14r | | 6x=2.2 | | 4(5c-1)-2=18c+6 | | 1=2a+b |

Equations solver categories